Pendidikan Politik oleh Dewan Perwakilan Daerah Partai Keadilan Sejahtera Kabupaten Kerinci - Rahayu, Windy; Rafni, Al (Journal of Civic Education, 2023)
This article seeks to elucidate the execution of political education by the Regional Representation Council of Partai Keadilan Sejahtera (PKS) in Kerinci Regency. The research methodology employed herein is descriptive qualitative in nature. The selection of informants utilized a purposive sampling technique. Data acquisition encompassed interviews and documentation studies. The validation of data employed a source triangulation technique. Data analysis involved reduction, presentation, and drawing conclusions. The findings revealed that PKS in Kerinci Regency executed political education both internally and externally. Their programs comprised various activities such as training, mentoring, seminars, socialization, and community service. Notably, PKS's political education encompassed not only political facets but also religious content, exemplified by activities like 'halaqoh' study sessions—an aspect integral to PKS as a da'wah party. Within their political education initiatives, the Regional Representation Council of PKS in Kerinci Regency has systematically structured a cadreization curriculum. Key factors supporting these educational endeavors encompass human resources, funding, facilities, and information, which are crucial considerations for the party to ensure smooth implementation. This study is limited to the PKS in Kerinci Regency. The further study should see the implementation of PKS in Indonesia and other Islam ideology in party and civil society organization.